Biocomputing approach in forensic analysis. Issue 1 (2nd January 2017) - Brunelle, Erica; Halámek, Jan
Abstract: Biochemical analysis of biological substances found at a crime scene is an important aspect of forensic investigations, where the objective is to determine the identification of crime victims and suspects/persons-of-interest. One particular biochemistry/molecular biology-based area of interest in forensic analysis is forensic serology; this area focuses on the complex task of gathering information regarding the type, age, ethnicity, and/or gender of the sample originator from the biological fluids (blood, saliva, etc.) found at a crime scene. In this review, we cover various studies involving biocomputing techniques used for the analysis of biological samples – namely blood – in different forensic applications. The studies covered include the differentiation of gender and ethnicity using a biocomputing system that produces a binary result, as well as the determination of blood spot age. Each of the applications showcased in this review produces sometimes ambiguous results that would normally pose major problems for a study, however, the addition of biocomputing logic provides an extra level of certainty and clarity. We hope to convey the advantages of utilizing biocomputing methods in various forms of forensic analysis.